Psychological Resilience Is Associated With Participation Outcomes Following Mild to Severe Traumatic Brain Injury - Wardlaw, Carla; Hicks, Amelia J.; Sherer, Mark; Ponsford, Jennie L. (Frontiers in Neurology, 2018)
Traumatic brain injury (TBI) causes physical and cognitive-behavioural impairments that reduce participation in employment, leisure, and social relationships. Demographic and injury-related factors account for a small proportion of variance in participation post-injury. Personal factors such as resilience may also impact outcomes. This study aimed to examine the association of resilience alongside demographic, injury-related, cognitive, emotional, and family factors with participation following TBI. It was hypothesized that resilience would make an independent contribution to participation outcomes after TBI. Participants included 245 individuals with mild-severe TBI (Mage=44.41, SDage=16.09; post traumatic amnesia duration M 24.95 days, SD 45.99) who completed the Participation Assessment with Recombined Tools-Objective (PART-O), Traumatic Brain Injury Quality of Life Resilience scale, Family Assessment Device General Functioning Scale, Rey Auditory Verbal Learning Test, National Adult Reading Test, and Hospital Anxiety and Depression Scale an average 4.63 years post-injury (SD 3.02, R 0.5-13). Multiple regression analyses were used to examine predictors of PART-O scores as the participation measure. Variables in the model accounted for a significant 38% of the variability in participation outcomes, F (13, 211) = 9.93, p < .05, R2 =.38, adjusted R2 =.34. Resilience was a significant predictor of higher participation, along with shorter PTA duration, more years since injury, higher education and IQ, and younger age. Mediation analyses revealed depression mediated the relationship between resilience and participation. As greater resilience may protect against depression and enhance participation this may be a focus of intervention.